TiVo - Tybout, Alice M.; Hennessy, Julie (London : SAGE Publications Ltd, 2017)
In 1999 TiVo was preparing to launch its digital video recorder (DVR) in the United States. The companys goal was ambitious: it hoped to revolutionize how Americans watched television and to become a central player in the emerging interactive TV industry.Although it had a technological advantage, TiVo faced one competitor (ReplayTV) and potential entrants such as Microsoft, so its success was far from guaranteed. Evidence suggested a bright future for the company, however; the concept had attracted $240 million in venture capital, and market research indicated a uniquely high level of consumer interest.TiVo needed to capture the first-mover advantage and build its sales and brand as quickly as possible to support the companys IPO, which was planned to take place within eighteen to twenty-four months. TiVos positioning at launch would play a key role in determining its success.
Originally published: Tybout, A. M., & Hennessy, J. (2005). TiVo. 5-104-024 Evanston, IL: Kellogg School of Management, Northwestern University.
Description based on XML content.
Keywords: elektronické knihy; electronic books; Interactive television -- United States; Home video systems -- Automatic control -- United States